2005
DOI: 10.1007/s10195-005-0086-5
|View full text |Cite
|
Sign up to set email alerts
|

Hip fractures in elderly patients treated with bipolar hemiarthroplasty: comparison between cemented and cementless implants

Abstract: A prospective, randomised study was conducted to evaluate the clinical and functional outcomes at 12 months of followup in two groups of patients affected by femoral neck fractures and treated with cemented or cementless bipolar hemiarthroplasty. Fiftythree cemented and 53 cementless prostheses were implanted on alternate days in 106 consecutive patients. We considered general demographic variables (age, sex, side of injury), operative delay, number of pre-existing conditions, ASA score, haemoglobin levels at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 20 publications
1
51
0
Order By: Relevance
“…There was no significant difference between the 2 groups of patients regarding most variables. S. Santini, et al [10] , Hansen 7 et al compared complications, reoperations and mortality and they did not find any statistically significant difference between the groups. Deangelis JP [11] et al found that in the treatment of nonpathologic displaced femoral neck fractures, the use of cemented and uncemented femoral components is associated with similar functional outcome at 6 months.…”
Section: Discussionmentioning
confidence: 95%
“…There was no significant difference between the 2 groups of patients regarding most variables. S. Santini, et al [10] , Hansen 7 et al compared complications, reoperations and mortality and they did not find any statistically significant difference between the groups. Deangelis JP [11] et al found that in the treatment of nonpathologic displaced femoral neck fractures, the use of cemented and uncemented femoral components is associated with similar functional outcome at 6 months.…”
Section: Discussionmentioning
confidence: 95%
“…1). A total of eight trials were included in this review [18][19][20][21][22][23][24][25]. There were 1,175 hips included in the 8 studies: 587 hips in the cemented group and 588 hips in the uncemented group.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…4,5,[7][8][9][10][11][12][13] Elderly patients with impaired cardiopulmonary function and pulmonary hypertension are especially at risk of cardiopulmonary complications. 14,15 Intraoperative fracture is a potential major complication of cementless hemiarthroplasty.…”
mentioning
confidence: 99%